2008
DOI: 10.1016/j.jmaa.2008.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Orthonormal bases and quasi-splitting subspaces in pre-Hilbert spaces

Abstract: Let S be a pre-Hilbert space. We study quasi-splitting subspaces of S and compare the class of such subspaces, denoted by Eq(S), with that of splitting subspaces E(S). In [D. Buhagiar, E. Chetcuti, Quasi splitting subspaces in a pre-Hilbert space, Math. Nachr. 280 (5–6) (2007) 479–484] it is proved that if S has a non-zero finite codimension in its completion, then Eq(S) = E(S). In the present paper it is shown that if S has a total orthonormal system, then Eq(S) = E(S) implies completeness of S. In view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This was partly proved in Ref. 6, where it was shown that if S admits an orthonormal basis (i.e., a total orthonormal set; we recall that a subset X of S is total if spanX is dense in S) then E q (S) = E(S) if, and only if, S is complete. (In particular, this means that E(S) E q (S) when S is an incomplete separable pre-Hilbert space.)…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This was partly proved in Ref. 6, where it was shown that if S admits an orthonormal basis (i.e., a total orthonormal set; we recall that a subset X of S is total if spanX is dense in S) then E q (S) = E(S) if, and only if, S is complete. (In particular, this means that E(S) E q (S) when S is an incomplete separable pre-Hilbert space.)…”
Section: Introductionmentioning
confidence: 87%
“…The question of when does a pre-Hilbert space admit an orthonormal basis was also studied in Ref. 6.…”
Section: Introductionmentioning
confidence: 99%
“…The members of E q (S) should behave somewhat similarly to the splitting subspaces but on the other hand, E q (S) (at least when S is separable) is always furnished with a "good supply" of infinite Boolean σ -subalgebras. In [6] it was proved that S is complete if, and only if, S admits an orthonormal basis and E(S) = E q (S). In particular, when S is separable, this result gives a proper strengthening of the Amemiya-Araki Theorem.…”
Section: C(s) E(s) E Q (S) F(s)mentioning
confidence: 99%
“…We would like to summarize and refine our recent results in this area, bring new illustrating examples, and outline problems for future research. This contribution has grown out of the papers [3,4,5,6,9,10,11,12,14,15,16]. For basic treatment on this field, the reader can consult also monographs [7,8].…”
Section: Introductionmentioning
confidence: 99%